Engineering multi-functionalized molecular skeleton layer for dendrite-free and durable zinc batteries. (August 2022) - Yu, Huaming; Chen, Yuejiao; Wang, Han; Ni, Xuyan; Wei, Weifeng; Ji, Xiaobo; Chen, Libao
Abstract: Aqueous Zn batteries are subject to uncontrollable dendrite growth and water-induced parasitic side reactions, resulting in poor Zn 2+ kinetics and limited lifespan. Herein, a self-consistent ultrathin multifunctional layer by integrating hydrophobic siloxane-based block and zincophilic diphosphate-building block into molecular skeletons on Zn foils (MTSi-Hedp-Zn) is proposed by a scalable and low-cost dip-coating technique. Experimental results combined with theoretical calculation (DFT) and COMSOL Simulations reveal that abundant O-Si-CH3 groups as hydrophobic block in the top of molecular skeletons is the contributing factor in precluding solvated H2 O corrosion. Zincophilic PO bonds on organic phosphate block in the backbone work as attraction area for fast Zn 2+ adsorption and transport kinetics. Simultaneously, such a combination enables surface-preferred (002) crystal planes on Zn metal, synergistically homogenizing the electric field at the interface and achieving preferentially flat growth without dendrites and side reactions. Accordingly, the MTSi-Hedp-Zn electrode exhibits an extended lifespan of over 2000 h and a much low voltage polarization of ~24.3 and 67.5 mV at 1 and 10 mA cm −2, respectively. Practical full cells coupled with commercial cathodes (CNT/MnO2 and V2 O5 ) both perform much better capacity retention than the bare Zn case. The proposed hydrophobic-zincophilic interface by silane-organic phosphoric acid provides a significant construction tactic for designing dendrite-free and corrosion-free Zn electrodes and beyond. Graphical Abstract: ga1 Highlights: A self-consistent ultrathin multifunctional layer on Zn foils via a simple and low-cost dip-coating technique is proposed. Abundant O-Si-CH3 groups in the top of molecular skeletons as hydrophobic block effectively preclude the solvated H2 O erosion. Zincophilic PO bonds in the backbone work for fast Zn 2+ adsorption and transfer kinetics on anode. The MTSi-Hedp-Zn electrode achieves an extended lifespan of over 2000 h and a much low voltage polarization of ~24.3 mV.